2020
DOI: 10.1007/s00270-020-02648-6
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Model for Freedom from TLR from a Multi-study Analysis of Long-Term Results with the Zilver PTX Drug-Eluting Peripheral Stent

Abstract: Purpose Develop a prediction model to determine the impact of patient and lesion factors on freedom from target lesion revascularization (ffTLR) for patients who are candidates for Zilver PTX drug-eluting stent (DES) treatment for femoropopliteal lesions. Methods Patient factors, lesion characteristics, and TLR results from five global studies were utilized for model development. Factors potentially associated with TLR (sex, age, diabetes, hypertension, hypercholesterolemia, renal disease, smoking status, Ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…15 In a recently developed freedom from target lesion revascularization (fTLR) prediction model for Zilver PTX DES candidates, Dake et al identified several baseline factors, including sex, age, Rutherford class, and prior intervention, as significantly predictive of loss of fTLR through 5 years (using records of 2227 patients who underwent Zilver PTX DES implantation for FP lesions). 16 Anatomic variables found to be predictive of loss of fTLR were lesion length, RVD, and presence of a CTO.…”
Section: Discussionmentioning
confidence: 99%
“…15 In a recently developed freedom from target lesion revascularization (fTLR) prediction model for Zilver PTX DES candidates, Dake et al identified several baseline factors, including sex, age, Rutherford class, and prior intervention, as significantly predictive of loss of fTLR through 5 years (using records of 2227 patients who underwent Zilver PTX DES implantation for FP lesions). 16 Anatomic variables found to be predictive of loss of fTLR were lesion length, RVD, and presence of a CTO.…”
Section: Discussionmentioning
confidence: 99%